Analisis Produktivitas Unit Redrying dengan Pendekatan Objective Matrix dan Analytic Hierarchy Process di PT XYZ - Deni, Deni; Rusindiyanto, Rusindiyanto (BRILIANT: Jurnal Riset dan Konseptual, 2025)
The redrying unit is a tobacco drying unit at PT XYZ that functions to enhance aroma, ensure safe storage, and re-dry tobacco with the appropriate moisture level. In recent months, the redrying unit at PT XYZ has experienced a decline. The company management suspects that the decline in productivity is caused by problems with the efficiency of the production process. Therefore, a productivity analysis was conducted to determine the level of tobacco productivity at PT XYZ. In this study, the objective matrix (OMAX) productivity method was used. The weighting of criteria is measured using Analytical Hierarchy Process (AHP). Based on the calculation results, the criteria of electrical energy, machine hours, labor, and raw materials have the highest partial productivity values of 1.22, 3.35, 10.57, and 98, respectively. The highest total productivity was achieved in the March 3 period at 650.7 and the lowest productivity in the November 9 period at 68.6. Improvements are made on all criteria, by applying the objective matrix method, PT XYZ is expected to increase the partial productivity and total productivity of the company in the future.